Wideband Ring-Monopole Flexible Antenna with Stub for WLAN/C-Band/X-Band Applications - Lee, Hoosung; Park, Yong Bae (Applied Sciences (Switzerland), 2022)
In this paper, we designed a flexible antenna operating in the WLAN/C-band/X-band and analyzed the antenna bending characteristics. It is advantageous to have a wide bandwidth because the resonant frequency of the flexible antenna can be changed when it is bent. The proposed antenna was designed based on a ring monopole antenna with broadband characteristics. Slots and t-strip lines to the ring, stubs to the feed, and stepped structures to the ground plane were added to increase bandwidth. As a result of analyzing the characteristics of the proposed antenna when bent through the S-parameter, it was confirmed that the proposed antenna is suitable at the target frequency, even if it is bent. The size of the antenna is 0.256 λ × 0.32 λ × 0.0016 λ ( (Formula presented.) ) at 2.4 GHz, and the antenna bandwidth is 15.68% (2.36 GHz~2.87 GHz) at 2.615 GHz and 111.69% (3.4 GHz~12 GHz) at 7.7 GHz.
Keywords: CPW-feed; flexible antenna; ring-monopole antenna; slot-ring antenna; stub matching; wideband antenna